Racial Valuation: Cultural Gatekeepers, Race, Risk, and Institutional Expectations of Success and Failure. (14th April 2020) - Erigha, Maryann
Abstract: Racial inequality persists in culture industries, despite increases in representation. Focusing on the Hollywood film industry, this research analyzes written correspondence to understand how, in their discourses, cultural workers as intermediaries or gatekeepers construct ideas about race to make predictions about economic value, success, and failure of cultural products. Findings demonstrate that cultural workers make racial valuations, or race-based judgments about the economic worth of cultural products—in this case by associating white actors with low economic risk, increased chances of profitability, and the expectation of success and linking black actors to high economic risk, decreased chances of profitability, and the expectation of failure. This practice of racial valuation disrupts conventional logics that emphasize the financial ambiguity of cultural markets to advance white institutional logics that invoke raced-based projections about a cultural product's expected performance. Ultimately, these racially biased assessments affect people, products, and processes along the film production, distribution, and consumption spectrum, especially privileging white workers and limiting Black workers in foreign markets, thereby creating and reinforcing unequal racial outcomes within culture industries.